Deadjectival Nouns with Suffixes {-ity} and {-ness} in English News: a Corpus-based Study - Khairumi, Nurul; Jati Kesuma, Tri Mastoyo (SUAR BETANG, 2024)
This research is a descriptive qualitative study that analyzes the frequency and collocations of deadjectival nouns that have suffixes {-ity} and {-ness} in English news. The data source is 100,000 English news sentences from 2023 retrieved from Leipzig Corpora Collection. The analysis was conducted with the assistance of AntConc. The results show that the suffix {-ity} tends to produce deadjectival nouns that dominantly appear in English news, while the suffix {-ness} tends to create a variety of nouns. In addition, the deadjectival nouns with the suffix {-ity} are more diverse in collocating, with 37 collocates, while the suffix {-ness} has 28 collocates. The suffix {-ity} collocates more frequently with grammatical words, forming grammatical collocation pattern type G1 in some of its collocates. In contrast, the suffix {-ness} is likely to collocate with other nouns and form compound words. Both suffixes tend to appear in nominal phrase constructions, as shown by the high occurrence of the conjunction ‘and’ according to the likelihood in AntConc statistics. This finding indicates that in sentence construction, both suffixes {-ity} and {-ness} frequently occur in coordinative form alongside with other nouns.